(3GdcTa Yf efGgL GdCOdI aj YbGFO GdedIs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s ((3eOjfI GdeQjI s)
(3ChdgG (B:s
(3hHYO MeO Gddg GdPi ENJU ef jTGA HMceJg abO QCjJ Cf CaMU ai gPG GdcJGH Yf GdXGgQ ef GdYbGFO GdJi bUO GdTQY Med GdLeghQ YdjgG s
(3BNQgG (B:s
(3hGdZQV GdPi bUOfGg ai gPG GdcJGH abO EfbVi hGddg Gdehab ddUhGH hcGf GdaQGZ efg ai SfI NeS hSHYjf hNeSeGFI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3hgj ef cJH GdCejQ RjOGf GdMSfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B228s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds